Studies on elements diffusion of Mn/Co coated ferritic stainless steel for solid oxide fuel cell interconnects application - Zhang, Hui; Wu, Junwei; Liu, Xingbo; Baker, Andrew (International journal of hydrogen energy, 2013)
The spinel structure of manganese cobalt oxide (Mn,Co)3O4 is one of the most promising coatings for solid oxide fuel cell (SOFC) stainless steel interconnects. The stoichiometric Mn1.5Co1.5O4 composition has properties that are preferable to other Mn/Co ratios, for example a higher conductivity and a thermal expansion coefficient that matches the typical steel substrate. However, previous work showed the Mn/Co ratio changes during operation due to the diffusion of Mn from the substrate. The results presented here are on three coatings with different compositions (namely; pure Co, Mn20Co80, and Mn40Co60) with each coating composition deposited to a thickness of 800 nm, 1500 nm, and 3000 nm. The coatings were applied by DC magnetron sputtering and then machine cut into coupons for isothermal annealing at 800 °C in air using a batch-type furnace for 2, 10, 50, 250, and 1000 h. The morphology, chemical composition (including surface and cross sections of the layers) and structures of the oxides formed were analyzed by SEM, EDS and XRD. Analysis of the element diffusion (Mn, Co, Cr, Fe) shown here points to an optimized coating recipe of Mn40Co60. ► We optimized coating composition by taking into account of elements diffusion. ► Fe, Cr, Mn outward diffusion and Co inward diffusion were confirmed. ► Outward diffusion rates follow the order of DMn > DFe > DCr. ► Optimized coating composition was proposed to be Mn40Co60.